Exploring Competence as a Moderating Factor in the Relationship Between Training, Education, and Employee Performance - Muhlis; Ibnu Qizam; Erika Amelia; Yusar Sagara; Ajib Akbar Velayaty (CV. Creative Tugu Pena, 2026)
This study examines the effects of education and training on employee performance and evaluates the moderating role of competency in the Islamic banking sector in the digital era. A quantitative approach was employed, with data collected through validated and reliable questionnaires from 100 employees of Bank Muamalat Indonesia Makassar. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that education and training have positive and significant effects on employee performance, with training demonstrating a stronger influence. These findings support Human Capital Theory, which emphasizes education and training as strategic investments to enhance productivity and professional capability. However, competency was not found to moderate the relationships between education, training, and performance, suggesting that individual competency does not necessarily strengthen the effectiveness of human capital investments. This finding highlights the importance of organizational systems and contextual alignment in optimizing human resource development. The study recommends that Islamic banking institutions implement structured education and value-based training to support sustainable performance. Future research is encouraged to involve broader samples across Islamic banking institutions, apply mixed-method approaches, and incorporate contextual factors such as religiosity or workplace spirituality to provide a more comprehensive understanding of employee development effectiveness.